Prevalence, Awareness, Treatment, and Control and Related Factors of Hypertension in Multiethnic Agriculture, Stock-Raising, and Urban Xinjiang, Northwest China: A Cross-Sectional Screening for 47000 Adults. (3rd November 2019) - Wang, Lin; Li, Nanfang; Heizhati, Mulalibieke; Yao, Xiaoguang; Duiyimuhan, Gulinuer; Zhou, Keming; Cao, Mei; Wang, Menghui; Hu, Junli; Zhang, Delian
Abstract : Background . Hypertension is the leading cause of cardiovascular disease. Distribution of hypertension and related factors among multiethnic population in Northwest China remains scarce. The aim was to determine prevalence, awareness, treatment, control, and risk factors associated with hypertension among multiethnic population in Northwest China. Methods . We conducted a blood pressure (BP) screening project covering a third of adults in Emin Xinjiang, Northwest China, during 2014–2016. Hypertension was defined as systolic BP ≥ 140 mmHg, diastolic BP ≥ 90 mmHg, and/or taking antihypertension drugs. We compared prevalence, awareness, treatment, and control of hypertension and related factors by different regions (agriculture, stock-raising, or urban) and by ethnic groups. Results . Totally 47, 040 adults were screened with 48.5% women. Overall prevalence, awareness, treatment, and control of hypertension were 26.5%, 64.6%, 44.5%, and 15.3%, respectively. Age-gender-adjusted hypertension prevalence was higher in urban (28.2%) than in other regions and in Kazakh (30.3%) than in others. The lowest awareness and treatment rates were observed in the agricultural region and in Kazakh subjects, while the lowest control was in the stock-raising region (13.8%) and in Kazakh subjects (12.6%). After adjusting for age, gender, ethnicity, and regions, compared to normal weight, nonsmokers, and nondrinkers, obesity, smoking, and alcohol intake were significantly related to increased prevalence of hypertension by 94%, 1.5, and 3.9 folds, respectively. Conclusions . Disparities in hypertension control among regions and ethnic groups suggested inadequate screening and treatment, especially in stock-raising regions and Kazakh populations. Control of alcohol intake, smoking, and obesity should be at high priority of health promotion.